Isolation of antidiabetic compounds from tetracera Indica - Ahmed, Qamar Uddin; Hasan, Md. Mahmudul (Stu); Mat So'ad, Siti Zaiton; Tengku Zakaria, Tengku Muhamad Faris Syafiq; Bakhtiar, M. Taher; Latip, Jalifah; Ahmad, Farediah; Sarian, Murni Nazira (2016)
Mempelas paya (Tetracera indica) is a rain forest climber of Malaysia which is traditionally used to treat various ailments including diabetes and its related infirmities. The objective of this research was to explore an in vitro antidiabetic activity of the stems of T. indica as well as to isolate the active principles responsible for its in vitro antidiabetic effect. In vitro antidiabetic evaluation was done on 3T3-L1 pre-adipocytes and adipocytes. Two flavones (wogonin and norwogonin) were isolated from the stems ethanol extract of T. indica and subjected to cytotoxicity test against 3T3-L1 adipocytes with regard to evaluate their antidiabetic potential. Both flavones were isolated and purified through silica gel and sephadex LH-20 column chromatography and their structures were elucidated through 1H-and 13C-NMR spectroscopy. Cytotoxicity test was performed through MTT assay on 3T3-L1 pre-adipocytes to determine the safe dose for further in vitro antidiabetic evaluation. The stems ethanol extract, fractions and both flavones were further subjected to adipogenesis to investigate insulin like activity or insulin sensitizing activity for the purpose of evaluating antidiabetic activity. Both flavones were introduced to the cells in three different safe concentrations as well as in different adipogenic cocktails. The adipogenic cocktails were modified by the compounds and rosiglitazone in the presence or absence of insulin. Results showed that both flavones induced adipogenesis like insulin and enhanced adipogenesis like rosiglitazone significantly. Furthermore, both flavones as well as rosiglitazone as positive control were subjected to fluorescence glucose uptake test by 2-NBDG (fluorescent glucose analog) on mature adipocytes. Results suggested significant glucose uptake activity by both flavones. It is suggested that further in depth study on both flavones might help to discover new safe antidiabetic agents. Keywords: Tetracera indica Merr., Dilleniaceae, Flavones, 3T3-L1 Adipocyte, Adipogenesis